Learning Strategies and Innovations among Medical Students in the Philippines during the COVID-19 Pandemic - Cedeño, Trisha Denise D.; Rocha, Ian Christopher N.; Ramos, Kimberly G.; Uy, Noreen Marielle C. (International Journal of Medical Students, 2021)
This paper highlights the experience of graduating medical students or clinical clerks in the Philippines during the COVID-19 pandemic. For instance, clinical clerks are supposed to be having their actual face-to-face patient encounters in the hospital setting. It is during the clinical clerkship, the final year of a four-year medical degree program, that a medical student applies his or her theoretical knowledge in practice. However, due to the pandemic, changes needed to be done in order to ensure continuous learning despite having to have little to no contact with actual patients. Hence, in this paper, various learning strategies and innovations have been presented to give examples of how Filipino medical students or clinical clerks tried to cope and adapt with the changes in the mode of learning in the medical field.